Ethics and Health - Lucio Mango; Giorgio Ascoli (Journal of Public Health International, 2017)
A perspective on public health ethics discusses fairness, autonomy, and solidarity in policy making. It illustrates dilemmas in resource allocation and risk communication.
Keywords: public health ethics